Household finances and social comparison: Determinants of financial well-being in Indonesia - Ghina, Aisyah Amatul; Sukarno, Subiakto (Journal of Socioeconomics and Development, 2021)
To achieve a vision of sustainable financial well-being (FWB) in Indonesia, generating more knowledge in household behavior and FWB is pivotal. This study assesses the impact of household financial position and social comparison on individual FWB in Indonesia. Using the latest wave of Indonesia Family Life Survey (IFLS) dataset, subjective FWB assessed by questions on subjective prosperity, perceived current standard of living adequacy and perceived future standard of living. The empirical analysis shows that net wealth and total assets are also essential determinants and positively related to FWB along with income. On the contrary, though it is only found significant on the perceived current standard of living adequacy, the total debt level has a negative effect on FWB. The findings also confirm that socioeconomic and demographic factors also significantly affect FWB (e.g., being female and more educated has a positive effect on FWB). Furthermore, it also found that relative financial position (i.e., social comparison) has important roles in determining individuals' FWB level. Being above the reference group's average for a particular financial measure (i.e., income and total assets) has a positive effect on an individual's FWB. The findings of this study suggest for promoting financial education in the national school system starting senior high school to increase the level of financial well-being among young adult and people with lower educational attainment. JEL ClassificationÂ C31; D14; I31